Applied probability and stochastic processes - Beichelt, Frank, 1942- author (CRC Press, Taylor & Francis Group, 2016)
Beichelt offers numerous worked examples to represent stochastic processes in a user-friendly way. He includes a review of probability-theoretic topics and provides important proofs and theoretically challenging examples for the mathematically interested reader.